Old Curses, New Approaches? : Fiscal Benchmarks for Oil-Producing Countries in Sub-Saharan Africa - Olters, Jan-Peter (IMF Working Papers; Working Paper ;, 2007)
Buoyant oil prices have allowed oil-producing countries in sub-Saharan Africa (SSA OPCs) to increase oil exports and fiscal revenues, providing them with resources necessary to address the pressing social needs. To preclude another boom-bust cycle, this paper advocates the definition of a fiscal benchmark anchored in sustainability grounds, following Leigh- Olters (2006). The difference between current primary deficits and those that could be maintained after oil reserves are exhausted represent an indication of the degree to which fiscal positions will have to be adjusted-either gradually, while the overall balances remain in surplus, or abruptly, once oil revenues begin to dwindle.